WWI in John Dos Passos' Novels - Bauer, Vojtěch (Univerzita Pardubice, 2019)
This bachelor thesis focuses on the topic of First World War in the novels One Man's Initiation: 1917 and Three Soldiers by John Dos Passos. This paper provides literary context of John Dos Passos and a brief summary of the American involvement in the First World War. Then it explains several crucial terms for this thesis such as trench warfare and shell shock and subsequently analyses them in both aforementioned novels. Also, this thesis analyses the literary techniques used in both novels and tries to explain their usage.
Obraz první světové války v díle Johna Dos Passose
Keywords: první světová válka; Dos Passos, John; zákopová válka; shell shock; First World War; Dos Passos, John; trench warfare; shell shock